Amplification and sequencing of mitochondrial rRNA from Lutzomyia spp. vectors of leishmaniosis - URIBE, SANDRA; PORTER, CHARLES; VÉLEZ, IVÁN DARÍO (Revista Colombiana de Entomología, 1998)
Recent investigations have been suggested mitochondrial DNA as an important tool in molecular entomology studies that include not only species identification. but also establishment of phylogenetic anZI evolutive relationships among insects. In this work we amplified and sequenced a fragment of 380 pHs from the mitochondrial ribosomal large subunit; this preliminary work was done in order to obtain sequences with potential use as a taxonomic character in sand flies. Primers used for PCR amplification and DNA sequencing were designed based on the consensus sequence of insects previously reported for this region. A bias toward adenine and thymine (81%) is consistent with the base composition of mtDNA sequences of other insects. Multiple alignments among sequences did not show ambiguities characteristic of nuclear DNA and preliminary comparisons suggest their utility as a taxonomic character at the species level.